2019
DOI: 10.5539/ass.v15n3p73
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and English Language Proficiency in the Chinese Context

Abstract: The employment problem of college graduates has evoked concern around the world, which is particularly prominent in China in recent years. At the same time, English language proficiency of Chinese college students has been emphasized within their university academic requirements as well as from prospective employers. The consequent market pressure on Chinese college students to obtain language qualifications has created an environment where not only the utility, but also the symbolic value of English proficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Because past research has found human capital to be associated with positive employment outcomes (Luo and Daly, 2019), we expected the human capital variable of English language proficiency to moderate the serially mediated relationship between parental career support and their child's career outcomes. Contrary to both human capital theory (Becker, 1964) and prior studies of the positive influence of other human capital variables on career success (Ullah and Arslan, 2022), English proficiency did not moderate the serial mediation involving either career satisfaction or employment status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because past research has found human capital to be associated with positive employment outcomes (Luo and Daly, 2019), we expected the human capital variable of English language proficiency to moderate the serially mediated relationship between parental career support and their child's career outcomes. Contrary to both human capital theory (Becker, 1964) and prior studies of the positive influence of other human capital variables on career success (Ullah and Arslan, 2022), English proficiency did not moderate the serial mediation involving either career satisfaction or employment status.…”
Section: Discussionmentioning
confidence: 99%
“…Those with high levels of human capital are more effective at setting realistic career goals, making better career decisions and matching themselves to suitable employment opportunities (Baruch et al, 2005). Students with higher human capital are more successful in their STWT and have better employment opportunities (Luo and Daly, 2019).…”
Section: Serial Mediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the implications of HCT and treating English the language as a tool to enhance the chances and opportunities to be employed, prior studies examined whether English proficiency (e.g., Chandramohan et al, 2011;Luo & Daly, 2019) or studying in Englishmedium instruction programmes (Erling, 2017) would have any impact and increase individual capital in the job market and workplace. Their findings implied that both being proficient in English and a graduate of EMI programmes might increase opportunities and income in the workplace.…”
Section: Human Capital Theorymentioning
confidence: 99%